Comparative Study of the Effectiveness of Online and Offline Learning Methods in the Islamic Communication and Broadcasting Study Program Class of 2020 as a Trial Class in 2021 - Muhammad Ikbal Husma; Rahmiati Rahmiati; Nur Fadillah Amir; Muh. Khaerul; Andi Dian Fitriana; Nurhakki Nurhakki (State Islamic Institute of Bone, Indonesia, 2022)
This study focuses on comparing the effectiveness of online and offline learning methods in the 2020 Islamic Communication and Broadcasting study program as a trial class in 2021. This study uses the Uses and Gratification method. This research was conducted using the Quantitative Comparative method. Based on the results of the study, it was found that the offline learning method has a higher effectiveness than the online learning method on KPI Students Class of 2020 as a trial class in 2021, this is evidenced by comparative quantitative calculations carried out by researchers in which the variable y shows a higher value. compared to variable x. This research is limited to one class in the study program at IAIN Parepare, therefore it is recommended that further research can expand the scope of the subject.